Improvement in the structural and optical properties of Cu2SnS3 (CTS) thin films through soft-annealing treatment. (February 2020) - Olgar, M.A.
Abstract: In this work, Cu2 SnS3 thin films were synthesized by soft-annealing treatment of Cu and Sn film layers at various temperatures (200, 250, 300, and 350 °C) deposited on molybdenum-coated glass (Mo/Cu/Sn) employing sequential sputter deposition technique followed by sulfurization process at 550 °C utilizing RTP. Effect of the soft-annealing treatment and temperature on the compositional, structural and optical properties of CTS thin film was examined using EDX, XRD, Raman spectroscopy, SEM, and optical spectroscopy techniques. All CTS films demonstrated Cu-poor composition regardless of the soft-annealing treatment according to EDX measurements. Irrespective of the soft-annealing temperature, all samples showed formation of monoclinic crystal structure of CTS phase and some secondary phases in their XRD patterns. It was found that the sample soft-annealed at 250 °C had more desired crystalline quality amongst the other prepared samples. Formation of the CTS structure was confirmed by Raman spectroscopy measurements. SEM images of the samples demonstrated denser and smoother microstructure by raising the soft-annealing temperature up to 250 °C. Optical band gap of the films showed variation between 0.85 eV and 0.90 eV that may be influenced by crystalline quality of the films. Highlights: CTS thin films were grown on Mo-coated glass by sputtering process. Soft-annealing treatment was performed to Mo/Cu/Sn structure at various temperatures. Sulfurization process was carried out at 550 °C using RTP. All CTS samples demonstrated Cu-poor composition. Soft-annealing at 250 °C presented promising results for solar cell applications.